MON-615 Seasonal Changes in Thyroid Function in Healthy Subjects in Japan: Analysis of 8,489 Health Check Participants - Yamada, Sayaka (J Endocr Soc, 2019)
Aim: Thyroid hormone affects the whole-body metabolism, including that of lipids and glucose, and its involvement in NAFLD / NASH has recently been reported. Accurate evaluation of thyroid function is therefore important. In this study, seasonal changes in thyroid function in approximately 10,000 health check participants were investigated, and the effects of age and smoking were also examined.Subjects and methods: The subjects were participants of medical checkups at Hidaka Hospital from 2007 to 2013. Exclusion criteria were a past history of thyroid disease, steroid use, renal failure and liver cirrhosis. To exclude the effects of menstruation, we examined 8,489 men whose blood TSH and FT4 values were within the reference values for monthly changes in thyroid function, and the effects of age and smoking. All blood TSH and FT4 levels were measured at 8 ~ 9:00 AM after over night fasting.Results: The average age was 49 ± 10 years old. The number of participants varied each month, with a minimum of 346 in April and a maximum of 961 in November. The highest median serum TSH level was 1.6 μU/ml in January (winter), and the lowest was 1.3 μU/ml in June, July, August and September (summer). These values were significantly different from the yearly median value of 1.4 μU/ml in April and November. On the other hand, the FT4 level was significantly lower in August than in the other months except for February. The extents of seasonal changes in TSH and FT4 levels were reduced in elderly subjects >60 years old. Furthermore, the median blood TSH level of 2,262 smokers was lower than that of 4,709 non-smokers (median: smoker, 1.2μU/ml vs. non-smoker, 1.5μU/ml). However, seasonal changes were also observed in smokers. Conclusions: This is the first report in a large healthy cohort demonstrating that there are significant seasonal changes in thyroid function including freeT4 levels. Several factors, such as season, age, smoking and gender, need to be taken into account for accurate evaluation of thyroid function.